Analysis of dimensionality Reduction Using Principal Component Analysis (PCA) and Two Dimensional Haar Wavelets (International Journal of Food and Nutritional Sciences, 2019)
Due to advances of digital technology in all sectors ranging from healthcare, production, weborganization a huge data had been generated through these domains. Machine learning algorithmsare used to uncover the hidden features of these data. The main curse of these data is that, it alsogenerates huge volume of redundant data